100 poets a little anthology - Carey, John 1934- (Yale University Press, 2021)
"A poem seems a fragile thing. Change a word and it is broken. But poems outlive empires and survive the devastation of conquests. Celebrated author John Carey here presents a uniquely valuable anthology of verse based on a simple principle: select the one-hundred greatest poets from across the centuries, and then choose their finest poems. Ranging from Homer and Sappho to Donne and Milton, Plath and Angelou, this is a delightful and accessible introduction to the very best that poetry can offer. Familiar favorites are nestled alongside marvelous new discoveries--all woven together with Carey's expert commentary. Particular attention is given to the works of female poets, like Christina Rossetti and Charlotte Mew. This is a personal guide to the poetry that shines brightest through the ages. Within its pages, readers will find treasured poems that remain with you for life"--
Keywords: Poetry / Collections; Poetry; Poésie / Collections; POETRY / Anthologies (multiple authors); poetry; Collections; Poésie